Serial functional communication training: Extending serial DRA to mands and problem behavior. (14th August 2017) - Lambert, Joseph M.; Bloom, Sarah E.; Samaha, Andrew L.; Dayton, Elizabeth
Abstract: Functional communication training (FCT) is commonly used to eliminate problem behavior. Not surprisingly, the efficacy of the intervention depends on fidelity to programmed procedures. For instance, problem behavior is likely to resurge if caregivers fail to reinforce mands during the maintenance stages of FCT. Despite this, recent translational work on arbitrary human responses suggests that incorporating multiple‐mand instruction into a serial‐training format may increase the probability of a recency effect, and a reversion of response resurgence (both desirable outcomes when mands are the most recently reinforced responses prior to extinction). Although promising, this effect has not been replicated with socially significant human behavior. Thus, we compared the relative effect of traditional FCT with that of serial FCT on the resurgence of the problem behavior, and mands, of 2 children. In contrast to previous research, we observed primacy effects for both subjects (i.e., the magnitude of the resurgence of problem behavior was greater than it was for any subsequently trained mand), and mand resurgence never occurred for one subject. Notwithstanding these limitations, the percentage of total responding allocated toward the resurgence of problem behavior was less in the serial FCT component relative to the traditional FCT component, and we observed a reversion of response resurgence for one subject.